Development and clinical application of a endonuclease restriction real-time loop-mediated isothermal amplification (ERT-LAMP) assay for rapid detection of Haemophilus influenzae - Cheng, Jinzhi; Zhou, Yuhong; Zhao, Xue; Lu, Jingrun; Wu, Jiahong; Wang, Yu (Frontiers in Microbiology, 2022)
Haemophilus influenzae is a main human pathogen that results in a series of diseases in children and adults, such as pneumonia, bacteremia, and meningitis. Although there are many detection methods, they cannot meet the requirements of an early diagnosis. For the prevention and control of H. influenzae infection, quick, sensitive, and particular diagnostics are crucial. Loop-mediated isothermal amplification (LAMP) coupled with restricted endonuclease digestion and real-time fluorescence (H. influenzae-ERT-LAMP) detection was employed to diagnose H. influenzae. H. influenzae-ERT-LAMP combines LAMP amplification, restriction endonuclease cleavage, and real-time fluorescence identification into a single-pot reaction, allowing for the rapid identification of H. influenzae in 40 min. The outer membrane protein (OMP) P6 gene of H. influenzae was employed to build a sequence of H. influenzae-ERT-LAMP primers. The limit of detection (LoD) of H. influenzae-ERT-LAMP test was 40 fg of genomic DNA per reaction, and the non-H. influenzae templates did not provide positive outcomes. To investigate the applicability of H. influenzae-ERT-LAMP method in clinical sample detection, 30 sputum specimens were obtained from individuals suspected of being infected with H. influenzae. H. influenzae-ERT-LAMP outcomes were in total agreement with LAMP-LFB and PCR. The H. influenzae-ERT-LAMP assay provides rapid, accurate, and sensitive detection making it a promising screening strategy in clinical and basic lab settings.